2017
DOI: 10.3847/1538-4357/aa94ce
|View full text |Cite
|
Sign up to set email alerts
|

The Constant Average Relationship between Dust-obscured Star Formation and Stellar Mass from z = 0 to z = 2.5

Abstract: The total star formation budget of galaxies consists of the sum of the unobscured star formation, as observed in the rest-frame ultraviolet (UV), together with the obscured component that is absorbed and re-radiated by dust grains in the infrared. We explore how the fraction of obscured star formation depends on stellar mass for mass-complete samples of galaxies at 0 < z < 2.5. We combine GALEX and WISE photometry for SDSS-selected galaxies with the 3D-HST treasury program and Spitzer/MIPS 24µm photometry in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
210
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(245 citation statements)
references
References 98 publications
33
210
2
Order By: Relevance
“…The total SFR can be accounted for by adding both IR and UV estimates (SFR IR+UV ). Not surprisingly, the star formation is dominated by SFR IR , with SFR UV only contributing at the level of 2%-20% to the total SFR (SFR IR+UV ), in agreement with other previous works comparing obscured and unobscured star formation in starburst galaxies (e.g., Puglisi et al 2017) and galaxies with similar stellar mass (e.g., Whitaker et al 2017).…”
Section: Spatially Resolved Uv Slopessupporting
confidence: 78%
“…The total SFR can be accounted for by adding both IR and UV estimates (SFR IR+UV ). Not surprisingly, the star formation is dominated by SFR IR , with SFR UV only contributing at the level of 2%-20% to the total SFR (SFR IR+UV ), in agreement with other previous works comparing obscured and unobscured star formation in starburst galaxies (e.g., Puglisi et al 2017) and galaxies with similar stellar mass (e.g., Whitaker et al 2017).…”
Section: Spatially Resolved Uv Slopessupporting
confidence: 78%
“…where f obscured corresponds to the obscured fraction of star formation and SFR total corresponds to the total SFR of galaxies (the sum of the obscured and unobscured fraction). To calculate f obscured we use the empirical relation derived by Whitaker et al (2017) between the obscured fraction of star formation and the stellar mass for main-sequence galaxies in the redshift range from z = 0.5 to z = 2.5. We assume that this empirical fit extends towards higher redshift and also applies for galaxies above the main-sequence.…”
Section: Generating Mock Lightconesmentioning
confidence: 99%
“…All star-formation is obscured -We adopted the fit presented in Whitaker et al (2017) to estimate the obscured fraction of SF. An extreme alternative is to assume that all SF happens in dust environments and f obscured = 1.…”
Section: A Is the Flattening In The Number Counts Robust Against Thementioning
confidence: 99%
“…They also found that the relation does not undergo any redshift evolution. Since our sample lies at z 3, we decided to investigate how it compares with the lower-redshift sources of Whitaker et al (2017).…”
Section: Fraction Of Obscured Star Formationmentioning
confidence: 99%